2024
DOI: 10.1108/tr-06-2023-0428
|View full text |Cite
|
Sign up to set email alerts
|

Organizational politics and employee job performance in the tourism and hospitality industry: workplace stress and counterproductive work behavior

Bassam Samir Al-Romeedy,
Hazem Ahmed Khairy

Abstract: Purpose This study aims to explore how job performance (EJP) is affected by employees’ perception of organizational politics (POP). It also investigates the mediating roles of workplace stress (WS) and counterproductive work behavior (CWB). Design/methodology/approach Data was gathered from employees working in category (A) travel agencies and five-star hotels in Egypt. A partial least squares structural equation modeling analysis was conducted using 468 valid responses. Findings The findings indicate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Lastly, the findings reveal that eco-innovation has a positive impact on sustainable competitive advantage and positively mediates the relationship between digital leadership and sustainable competitive advantage. These findings are in line with previous research conducted by Kuo et al [102], Ismail et al [15], and Al-Romeedy and Khairy [103].…”
Section: Discussionsupporting
confidence: 93%
“…Lastly, the findings reveal that eco-innovation has a positive impact on sustainable competitive advantage and positively mediates the relationship between digital leadership and sustainable competitive advantage. These findings are in line with previous research conducted by Kuo et al [102], Ismail et al [15], and Al-Romeedy and Khairy [103].…”
Section: Discussionsupporting
confidence: 93%
“…A green organizational identity significantly boosts sustainable competitive advantage in tourism and hospitality organizations by embedding sustainability into the core values and operations of the business. This strong identity fosters a culture of environmental responsibility among employees, promoting consistent and innovative green practices [68,92]. It also enhances the organization's reputation among eco-conscious consumers, attracting a loyal customer base that values sustainability.…”
Section: Green Organizational Identity and Sustainable Competitive Ad...mentioning
confidence: 93%
“…Consequently, employees become effective ambassadors of the organization's green values, improving internal communication and collaboration on sustainability efforts. This internal promotion of green initiatives not only boosts morale and job satisfaction but also strengthens the organization's overall brand image, making it more appealing to eco-conscious consumers and stakeholders [68,69]. Hence, the following hypothesis is proposed: H2.…”
Section: Green Ambidexterity and Internal Green Marketingmentioning
confidence: 99%
See 1 more Smart Citation
“…Although work stress is a phenomenon that emerges under the influence of various factors, it also has negative consequences for employees and businesses [14,15]. Previous studies have shown that work stress levels can affect employees' well-being [5], affective and normative commitment, job satisfaction [16], job performance [17], productivity [18], work alienation [19], depression, cardiovascular disease, cancer risks [20], turnover intentions [21], and burnout levels [22]. This study focuses on the work-related burnout problem, which is negatively affected by work stress, from among the aforementioned variables.…”
Section: Introductionmentioning
confidence: 99%